Markenselbstbild vs. Markenwahrnehmung: Kommt das neue Markenleitbild der BILD trotz eingeführter Paid Content-App auch in der Markenwahrnehmung des potentiellen Kunden an? - Julia Gäßler; Irene Kramer; Jens Pätzmann (Markenbrand, 2018)
– The following article deals with the question whether brands are able to successfully transfer their mission statement on the consumer perception due to their products. This topic will be analysed by means of the new brand concept of the German tabloid BILD. For determining the brand awareness of the potential customers, the valuations of the BILD smartphone app as well as a quantitative primary market research should give indication. For this purpose the respondents are separated into BILD readers and non-readers and get evaluated separately, in order to identify possible differences in the perception of the two groups. Especially the survey illustrates that on the one hand the research issue can be answered with yes, because BILD is capable to transmit its brand concept mainly on the potential customer. On the other hand, this is not possible for all brand aspects. In some areas the demand for optimization is still necessary for the Springer publishing house, because here the opinions among the target group differ significantly.
Keywords: 650